Characterization of viscoplasticity behaviour of P91 and P92 power plant steels - Saad, Abdullah Aziz; Hyde, T.H.; Sun, W.; Hyde, Christopher J.; Tanner, David W. J. (Elsevier, 2013)
This paper deals with the determination of material constitutive model for P91 and P92 steels at high temperatures. An isothermal, strain-controlled test programme was conducted for both steels for a temperature range between 400 and 675 °C. The experimental data from these tests were used to obtain the material constants in a viscoplasticity model. The model includes the effects of isotropic and kinematic hardening, as well as time-dependent effects, and has been used to model the cyclic material behaviour of each material. Material constants were initially determined from initial cycle stress–strain data, maximum stress evolution data and stress relaxation data. The material constants were improved by use of a least-squares optimisation algorithm. The constitutive models have been implemented into the ABAQUS finite element (FE) code by using the Z-mat software. The performances of the material models for both steels have been assessed by comparing predictions with experimental data obtained from the tests.